Dynamics of mangrove community in revegetation area of Karangsong, north coast of Indramayu District, West Java, Indonesia - HENDRA GUNAWAN; SUGIARTI SUGIARTI; SOFIAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2017)
Gunawan H, Sugiarti, Iskandar S. 2017. Dynamics of mangrove community in revegetation area of Karangsong, north coast of Indramayu District, West Java, Indonesia. Biodiversitas 18: 659-665. Mangrove along the north coast of Java is heavily degraded due to the conversion of land into fish ponds and human settlement areas. A revegetation program has been initiated by the local community of Karangsong Village, Indramayu District, West Java, Indonesia, supported by PT. Pertamina RU VI Indramayu. Our research aimed to study the population dynamics of the mangrove revegetation in Karangsong. Secondary data was collected from the Fishery and Maritime Services of Indramayu and PT. Pertamina. We carried out on-location field observations and we interviewed key respondents. Data was analyzed to describe trends in the diversity index and population dynamics of the mangrove. It was observed that the revegetation effort in the shoreline of Karangsong had covered Â± 69.08 hectares which consisting of six species of mangrove and three tree species of coastal vegetation i.e. Rhizophora mucronata Lam., Rhizophora stylosa Griff., Rhizophora apiculata Blume, Avicennia marina (Forssk.) Vierh., Avicennia alba Blume, Sonneratia caseolaris (L.) Engl, Terminalia catappa L., Casuarina equisetifolia L., and Ziziphus mauritiana Lam. The mangrove population increased dramatically, from estimated 25,000 individuals in 2008 to 690,835 individuals in 2016. Rhizophora mucronata was the most dominant species (68.85%), followed by Rhizophora stylosa (18.33%) and Rhizophora apiculata (9.53%). The Shannon diversity index was fluctuated but tend to be increased from 0.80 to 0.95.